Hubungan Antara Asupan Protein dengan Anemia Pada Remaja di Sukoharjo Jawa Tengah - Safitri, Aulia Nanda, dr. M. Shoim Dasuki, M.Kes (2017)
Background: adolescence is a transitional stage from childhood to adulthood, which needs more nutrients for growth and development process. protein intake in adolescents is still quite low, whereas deficiency of protein intake can be one of anemia factors in adolescents. Objective: To analyze the correlation between protein intake with anemia in adolescents in Sukoharjo, Central Java Methods: The study design was observational analytic research methods with case control approach. Sampling technique used was purposive sampling, which were 28 peoples for each group. Data were analyzed using SPSS 18.0 for Windows with Chi-Square test analysis. results: After test analysis Chi-square found value significancy (P) was 0,009 which means there are significant relationship between the protein intake with anemia, it also obtained the value of the odds ratio (OR) was 3,973. conclusion: There are significant relationship between protein intake with anemia, where the adolescent with less protein intake has 3,973 times risk greater experience anemia compared with someone who has a protein that quite. Keywords: protein intake, anemia, adolescent